Evaluating the efficacy of various flocculants for sediment removal from high-turbidity water for micro-irrigation systems - ZHAO Ruiting; YAN Xinjun; WANG Xuehu (Guan'gai paishui xuebao)
【Background】Emitter clogging is a common issue in micro-irrigation systems, and effective sediment removal from irrigation water is crucial for maintaining system performance. This study experimentally assessed the performance of various flocculants in accelerating the sedimentation of muddy water.【Method】Water collected from the Tarim River was used for the experiments. The sediment removal efficiency of five flocculants, applied both individually and in combination, was compared. To identify the optimal flocculant formulation, a comprehensive evaluation was conducted using the Analytic Hierarchy Process (AHP) combined with the entropy weight method, considering both performance and cost.【Result】When applied individually, anionic polyacrylamide PAM(-) achieved the best sediment removal, with optimal performance observed at a concentration of 0.03 g/L. Among compound treatments, a 1∶1 mixture of polyaluminum chloride (PAC) and cationic polyacrylamide PAM(+) showed the most effective sedimentation at a concentration of 0.01 g/L. Overall, combined flocculant applications outperformed single-agent treatments.【Conclusion】Mixing flocculants at an appropriate ratio can significantly enhance the sedimentation of high-turbidity water, thereby reducing emitter clogging in micro-irrigation systems. These findings offer practical guidance for improving irrigation water quality through the effective use of flocculants.